衛星および現場観測によるリュツォ・ホルム湾定着氷の面積と氷厚の変動解析 - 舘山, 一孝; 星野, 聖太; 牛尾, 収輝; 田村, 岳史; Kazutaka, Tateyama; Seita, Hoshino; Shuki, Ushio; Takeshi, Tamura (2013)
Monitoring of ice thickness in the Lützow-Holm Bay had been carried out by using the Electro-Magnetic Induction device as a part of the Japanese Antarctic Research Expedition since 2000. In this region, land-fast ice had not broken up and its thickness had increased since 2007 winter. In 2011 and 2012 sprongs, icebreaker Shirase could not reach the Showa station due to very hard ice conditions. This study reports the fluctuation of land-fast ice extent and thickness derived from the satellite images and EM sensors, respectively. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object